VX-702 Ameliorates the Severity of Sepsis-Associated Acute Kidney Injury by Downregulating Inflammatory Factors in Macrophages - Han Y; Wang J; Zhang J; Zheng X; Jiang Y; Liu W; Li W (Journal of Inflammation Research, 2024)
Yue Han,* Jingyi Wang,* Jin Zhang,* Xi Zheng, Yijia Jiang, Wei Liu, Wenxiong Li Department of Surgical Intensive Care Unit, Beijing Chao-Yang Hospital, Capital Medical University, Beijing, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenxiong Li, Department of Surgical Intensive Care Unit, Beijing Chao-Yang Hospital, Capital Medical University, 8 Gongren Tiyuchang Nanlu, Chaoyang District, Beijing, 100020, People’s Republic of China, Tel +86 136 0109 7813, Email liwx1126@163.comPurpose: Sepsis-associated acute kidney injury (S-AKI) contributes to high mortality, but it is lack of specific treatments. We aimed to investigate the underlying mechanism of S-AKI and to identify target drugs to alleviate AKI.Methods: We establish a stable mouse model of S-AKI by Pseudomonas aeruginosa incision infection. Based on high-throughput sequencing and bioinformatics analysis, we investigated the underlying mechanism and selected the target drug (VX-702) for S-AKI. An in vitro model established by co-cultured of kidney tubular epithelial cell line (TCMK-1) cells with lipopolysaccharide (LPS)-induced leukemic monocyte/macrophage cells (RAW264.7), we explored the effect of VX-702 on S-AKI.Results: The data showed interleukin (IL)-6 and IL-1β were the hub genes, and the mitogen-activated protein kinase (MAPK) signaling pathway was the main pathway involved in S-AKI. Administration of VX-702 by oral gavage decreased the elevated concentrations of IL-6, IL-1β, serum creatinine, and blood urea nitrogen in mice with S-AKI. Moreover, VX-702 reduced the number of apoptotic cells in damaged kidney tissues. Cell viability was decreased, and the number of apoptotic cells was increased in TCMK-1 cells co-cultured with LPS-induced RAW264.7 cells compared to LPS-induced TCMK-1 cells. VX-702 treatment reversed this effect. VX-702 treatment reduced the levels of phosphorylated p38 MAPK and proinflammatory cytokines in RAW264.7 cells and the supernatant. VX-702 could bind IL-6, IL-1β and MAPK, and affect the binding of IL-1β and its receptor, as demonstrated by molecular docking.Conclusion: VX-702 ameliorated S-AKI by inhibiting the release of proinflammatory cytokines from macrophages, indicating its potential as a novel therapeutic for S-AKI treatment.Keywords: sepsis-associated acute kidney injury, VX-702, macrophages, inflammatory factor, MAPK